Autoimmunity and atherosclerosis - Frostegard, Johan (Henry Stewart Talks, 2007)
Autoimmunity, High risk of atherosclerosis in autoimmune diseases, especially systemic lupus erythematosus (SLE), Antiphospholipid antibodies and atherosclerosis, Association and risk factors for atherosclerosis and cardiovascular disease in SLE, Autoimmune mechanisms in atherosclerosis in general